Pengelolaan Media Pembelajaran Interaktif dengan Aplikasi Quizizz pada Mata Kuliah Bahasa Arab Profesi di UIN Raden Intan Lampung - Erni Zuliana (Bustanul Ulum Journal of Islamic Education, 2024)
The fundamental problem underlying this research is the low learning outcomes of students in the Arabic for Professional Purposes course. The purpose of this research is to identify improvements in students' learning outcomes. Based on pre-action data findings, it was observed that students' learning outcomes were low, which was caused by a lack of variation in the use of learning media. This study proposes utilizing interactive learning media supported by the Quizizz application. The method used is classroom action research (PTK) based on the Stephen Kemmis and McTaggart model, which consists of four stages: (a) plan, (b) action, (c) observation, and (d) reflection. The results of this study show an improvement in students' learning outcomes, with the first cycle achieving 51.43%and the second cycle increasing to 88.57%.